De novo Transcriptome Reveals Gene Changes in the Development of the Endosperm Chalazal Haustorium in Taxillus chinensis (DC.) Danser. (20th February 2020) - Wei, Shugen; Wan, Lingyun; He, Lili; Wei, Ying; Long, Hairong; Ji, Xiaowen; Fu, Jine; Pan, Limei
Abstract : Loranthus ( Taxillus chinensis ) is a facultative, hemiparasite and stem parasitic plant that attacks other plants for living. Transcriptome sequencing and bioinformatics analysis were applied in this study to identify the gene expression profiles of fresh seeds (CK), baby (FB), and adult haustoria tissues (FD). We assembled 160, 571 loranthus genes, of which 64, 926, 35, 417, and 47, 249 were aligned to NR, GO, and KEGG pathway databases, respectively. We identified 14, 295, 15, 921, and 16, 402 genes in CK, FB, and FD, respectively. We next identified 5, 480 differentially expressed genes (DEGs) in the process, of which 258, 174, 81, and 94 were encoding ribosomal proteins (RP), transcription factors (TF), ubiquitin, and disease resistance proteins, respectively. Some DEGs were identified to be upregulated along with the haustoria development (e.g., 68 RP and 26 ubiquitin genes). Notably, 36 RP DEGs peak at FB; 10 ER, 5 WRKY, 6 bHLH, and 4 MYB TF genes upregulated only in FD. Further, we identified 4 out of 32 microRNA genes dysregulated in the loranthus haustoria development. This is the first haustoria transcriptome of loranthus, and our findings will improve our understanding of the molecular mechanism of haustoria.